Application of hierarchical cascading technique to finite element method simulation in bulk acoustic wave devices. (12th June 2018) - Li, Xinyi; Bao, Jingfu; Huang, Yulin; Zhang, Benfeng; Omori, Tatsuya; Hashimoto, Ken-ya
Abstract: In this paper, we propose the use of the hierarchical cascading technique (HCT) for the finite element method (FEM) analysis of bulk acoustic wave (BAW) devices. First, the implementation of this technique is presented for the FEM analysis of BAW devices. It is shown that the traveling-wave excitation sources proposed by the authors are fully compatible with the HCT. Furthermore, a HCT-based absorbing mechanism is also proposed to replace the perfectly matched layer (PML). Finally, it is demonstrated how the technique is much more efficient in terms of memory consumption and execution time than the full FEM analysis.